HEALTH EQUITY IN URBAN SLUMS: BARRIERS TO MATERNAL HEALTHCARE ACCESS AND OUTCOMES IN DEVELOPING MEGACITIES - Ifania Ifania; Winda Dwi Lestari; Ferawati Ferawati; Sisi Amailia; Dika Maretika Sobari (Medical Studies and Health Journal (SEHAT), 2025)
Access to maternal healthcare remains a critical challenge for women living in urban slums of developing megacities. Rapid urbanization has created densely populated informal settlements with inadequate sanitation, limited healthcare infrastructure, and high maternal mortality. This study systematically reviews social, economic, and structural barriers to maternal healthcare access. Following PRISMA 2020 guidelines, 19 peer-reviewed articles (2010–2025) were analyzed using thematic coding guided by the Social Determinants of Health and Andersen Behavioral Model. Findings reveal that restrictive gender norms, stigma, and low health literacy limit utilization, while poverty, high transportation costs, and lack of insurance further impede access. Structural challenges, including insufficient facilities, poor transport, and non-inclusive policies, exacerbate inequities. These barriers interact, creating compounded challenges for women in urban slums. Addressing them requires integrated interventions, including financial support, community-based services, inclusive digital health solutions, and policy reforms. The study provides evidence-based insights to enhance maternal health equity and advance Sustainable Development Goal 3.